Good Rehabilitation Outcomes and Improved Nutritional Status After Treatment With the Japanese Herbal Medicine Ninjin'yoeito in an Elderly Patient With Hip Fracture and Sarcopenia: A Case Report - Morinaga, Akinori; Nakamura, Hiroki; Hattanmaru, Kenji; Rokot, Natasya Trivena; Kimura, Yoko; Ito, Takashi (Frontiers in Nutrition, 2020)
We report a case involving a 92-year-old man who successfully received treatment with ninjin’yoeito, a Japanese herbal medicine, during the rehabilitation phase after hip fracture surgery. The patient was diagnosed with a left femoral neck fracture and underwent surgery. Two weeks after surgery, he was admitted to a rehabilitation hospital. At that time, his height, weight, body fat percentage, muscle mass, and Functional Independence Measure (FIM) score were 167 cm, 61 kg, 34.1%, 38.2 kg, and 49, respectively. For 1 month after surgery (i.e., 2 weeks after admission to the rehabilitation facility), he received rikkunshito, a traditional Japanese herbal medicine also known as Kampo medicine, for appetite loss and underwent rehabilitation. However, his appetite loss showed no improvement, and rikkunshito (7.5g/day) was replaced with ninjin’yoeito (7.5g/day). Two months later, although the patient’s body weight and body fat percentage decreased to 56.5 kg and 21.1%, respectively, his muscle mass increased to 38.9 kg. Nutritional status evaluation indicated an improvement in the level of proteins such as transferrin, prealbumin, and retinol-binding protein, which reflected an increase in food intake. The FIM score improved from 49 to 105. No side effects were observed. The findings from this case suggest that ninjin’yoeito, which includes astragalus root and schisandra fruit, may be an effective treatment option for sarcopenia or frailty with appetite loss and impaired activities of daily living in aged patients.